Nörolojik Hastalıkların Tanı ve Tedavisinde Yenilikler - Aynal Ölçücüoğlu, Leyli Can; Karcı, Mehmet Türkay; Uluakay Kandemir, Arzu; Uçan Tokuç, Firdevs Ezgi; Dikbaş, Hüsniye Aylin; Özenç, Betül; Sarıca Darol, Elif; Akıncı, Tuba; Zeytin Demiral, Gökçe; Aksoy, Selma; Ataman Serim, Vedat; Şahbaz, Fatma Gülhan; et al. (Academician Publishing Book DOI Portal, 2023)
-